Interplay of Power Relations in Neeharika’s Yogmaya: A Foucauldian Discourse Analysis - Niraula, Tirtha Raj (Dristikon: A Multidisciplinary Journal, 2020)
This article aims at exploring how Neelam Karki Niharika‘s Yogmaya presents the complex web of power relations that comprise domination, submission, and resistance. It mainly draw son Michel Foucault‘s idea that power is pervasive, not just oppressive but productive as well. Viewed from the Foucauldian notion of power as a theoretical framework, the study reveals the interplay of dominant and counter discourses in propagating knowledge and truth that are constructed and reconstructed. The novel is treated as a site of struggle where the state power along with the discourses of religion, patriarchy, and gender roles prominently operate so as to suppress the voice of the dissent. Yogmaya, a rural woman of the humble background, continuously resists both verbally and physically against various forms of power in the face of threats. She exercises her power in the same way as those who traditionally believe they possess it. In this connection, the focus lies on the protagonist‘s persistent attempts of resistance through the bold interrogation of the hegemonizing discourses and regimes of truth. As the text under study is written in Nepali, I use transliteration and free translation in order to cite the lines for analysis.